Rules, Organizational Structures and Economic Performance: The case of Prosecco Cooperative Wineries in the Treviso Area - Onofri, Laura; Barisan, Luigino; Boatto, Vasco (Italian Review of Agricultural Economics, 2016)
The study performs an economic analysis of the rules that govern the organization of production within Prosecco cooperative wineries in the Treviso area, in order to assess the economic impact on the wineries performance and the ability of the institution to minimize transaction costs. We first present an economic discussion of qualitative and quantitative information gathered for the 16 cooperative wineries in the Treviso area. Then we present a theoretical framework for the economics of transaction costs of the cooperative wineries. Despite the “fame” of the cooperative winery of an inefficient, assistance-based institution, it emerges the profile of a complex structure, which seeks to incorporate the values of social and cultural cohesion and competitiveness in the markets, within the mission of a company. There is a strong link between regulation of quality standards and impacts on the winery economic performance. In the case of the winery, achieving mutualism is paradoxically favored by the maximization of profits and the ability to do business.